Criminology and the UN Sustainable Development Goals: The Need for Support and Critique. (23rd September 2017) - Blaustein, Jarrett; Pino, Nathan W; Fitz-Gibbon, Kate; White, Rob
Abstract: The UN Sustainable Development Goals address a number of criminological issues. This article accounts for why criminologists should contribute to this agenda in a way that might benefit the international development community. We acknowledge a heightened risk of crime in parts of the Global South but argue criminologists should cautiously embrace this agenda as a platform for achieving human and sustainable development outcomes. Supporting this agenda means assisting with the design, implementation and evaluation of projects that contribute to safe, just and sustainable societies. From a critical standpoint, it also means challenging harmful or inappropriate initiatives and resisting attempts to capitalize on this agenda for political gain. Both modes of engagement are informed by the values of 'caution', 'scepticism' and southern epistemologies. The article then proceeds to examine three areas where criminological research can make important contributions: building safe and just societies, eliminating gender-based violence and promoting environmental justice.